Genotype and environment interactions in Moe and Mor of Acacia Mangium - Mohd Noor, A. Ghani; Lokman, Ngah (2014)
This paper presents the effects genotype by environment interaction (GXE) on the wood strength properties of a 13-year-old Acacia mangium established at five sites in the state of Sarawak, Malaysia. The objective of this paper is to examine GXE interactions on the modulus of elasticity (MOE) and modulus of rupture (MOR) of five provenances planted at the five sites. Effects of provenance and site were found to be significant for both MOE and MOR. GXE interaction was highly significant in both traits which involved changes in ranking, indicating a strong influence on both MOE and MOR. GXE interaction has the highest component of variance relative to site and provenance component of variances i.e. 30.5% and 37.8% for MOE and MOR, respectively